Cathode lens spectromicroscopy: methodology and applications - Menteş, T. O.; Zamborlini, G.; Sala, A.; Locatelli, A. (Beilstein Journal of Nanotechnology, 2014)
The implementation of imaging techniques with low-energy electrons at synchrotron laboratories allowed for significant advancement in the field of spectromicroscopy. The spectroscopic photoemission and low energy electron microscope, SPELEEM, is a notable example. We summarize the multitechnique capabilities of the SPELEEM instrument, reporting on the instrumental aspects and the latest developments on the technical side. We briefly review applications, which are grouped into two main scientific fields. The first one covers different aspects of graphene physics. In particular, we highlight the recent work on graphene/Ir(100). Here, SPELEEM was employed to monitor the changes in the electronic structure that occur for different film morphologies and during the intercalation of Au. The Au monolayer, which creeps under graphene from the film edges, efficiently decouples the graphene from the substrate lowering the Dirac energy from 0.42 eV to 0.1 eV. The second field combines magnetism studies at the mesoscopic length scale with self-organized systems featuring ordered nanostructures. This example highlights the possibility to monitor growth processes in real time and combine chemical characterization with X-ray magnetic circular dichroism–photoemission electron microscopy (XMCD–PEEM) magnetic imaging by using the variable photon polarization and energy available at the synchrotron source.
Keywords: gold (Au); graphene; intercalation; low-energy electron microscopy (LEEM); magnetism; nanostructures; X-ray magnetic circular dichroism (XMCD); X-ray photoemission electron microscopy (XPEEM)